Semantics and Pragmatics - Hilma Fitriana; Aida Nur Amalina; Aidil Syah Putra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This critical review paper examines the distinct yet highly interconnected roles of semantics and pragmatics within the broader framework of modern linguistics, with particular emphasis on their application in contemporary academic discourse. Semantics primarily investigates the literal, conventional, and truth-conditional meanings of words, phrases, and sentences, whereas pragmatics explores how contextual factors, speaker intentions, shared knowledge, cultural backgrounds, and situational circumstances shape meaning during communication. Employing a qualitative, conceptual, and critical review approach, this study analyzes various forms of academic communication, including scholarly articles, peer-review comments, classroom discussions, seminar presentations, and editorial interactions, to illustrate how meaning is constructed through the interaction between linguistic forms and contextual interpretation. The analysis reveals that the boundaries between semantics and pragmatics are often fluid, dynamic, and mutually influential, particularly in academic settings where effective communication depends on both precise language use and contextual awareness. The findings further demonstrate that relying exclusively on literal meanings is insufficient to explain the complexity of human communication, as successful interpretation frequently requires consideration of implicit meanings, inferencing processes, politeness strategies, and discourse conventions. Therefore, an integrated perspective combining semantic and pragmatic principles provides a more comprehensive understanding of language use in academic environments. This paper concludes that mastering the semantics–pragmatics interface is essential for educators, students, researchers, and scholars to communicate effectively, interpret academic texts accurately, engage in critical discussions, and navigate the linguistic, social, and cultural complexities that characterize contemporary academic communication in increasingly globalized educational contexts.